THE SYMBOLIC MEANING OF THE TRADITIONAL ROOF IN THE HOUSES OF KARO NORTH SUMATERA, INDONESIA (Proceeding of the International Conference on Arts and Humanities, 2018)
The aesthetic elements of traditional house of Karo are divided into three parts. They consist of upper part, middle part, and lower part. This article explains about Gerga Siwaluh Jabu as Karo’s Traditional House, in Desa Lingga, North Sumatera, Indonesia. This article focuses on the roof as the upper part of the house. The roof has the historical, social and cultural background. The ornaments attached on the roof have some important roles in Karo’s community. The aim of this qualitative research is to encourage the awareness about the meaning beyond the symbols used in Karo’s house. Cultural study approaches were used in this research as well as that of the tradition aesthetic theory. The article provides different perspective towards the historical and traditional artifact as the cultural identity. Not only serve its aesthetic purpose, those aesthetic elements on the Karo’s house roof are also seen as the protector of the inhabitants.
Keywords: Aesthetic Elements; Traditional House; Karo; Gerga Siwaluh Jabu; Culture